SISTEM ABSENSI DOSEN MENGGUNAKAN QR CODE BERBASIS ANDROID - Fenty Kurnia Oktorina; Andri Nofiar (ABEC Indonesia, 2021)
Polytechnic of Kampar is one of the universities in the palm oil sector in Indonesia. Every learning process will require an attendance. Attendance at the Polytechnic of Kampar is still using paper or manually. The drawbacks of attendance using paper are the possibility that the attendance book can be lost or scattered, the absence of attendance when the attendance book is lost, attendance uses a sheet of paper when the attendance book is lost, the number of paper uses, and so on. To overcome this, in this digital era, a lecturer attendance application was made using an QRcode based Android. This application is designed using Android Studio version 4.0, Code Igneter Framework and MySQL as a database. Hopefully, the application that is built can help overcome the shortcomings of attendance manually. After being tested, it can be seen that this application can solve problems in the manually attendance in Polytechnic of Kampar, so that in general this application can run as expected.